A Simplified Impression Technique for a Flabby Maxilla - A Clinical Report - Maskey, Brijesh; Mathema, S.R.B.; Bhochhibhoya, A. (Journal of Nepalese Prosthodontic Society, 2018)
Flabby maxillary ridge is the most commonly encountered clinical condition during routine dental practice. The presence of these displaceable denture-bearing tissues often poses difficulty during fabrication of complete dentures resulting in compromised support, retention and stability. Many impression techniques and materials have been proposed in various literatures to help overcome this difficulty. These techniques vary in philosophies but are often quite time-consuming to perform, and rely on materials not commonly in use in contemporary dental practice. The purpose of this paper is to describe an impression technique for flabby ridges, using conventional impression material.